E.B. O'Callaghan, Laws and Ordinances of New Netherland, 1638-1674, at 33 (1868) - (:unkn) unknown (My University, 1642)
Ordinance Of The Director And Council Of New Netherland Against Drawing A Knife And Inflicting A Wound Therewith: No one shall presume to draw a knife much less to would any person, under the penalty of fl.50, to be paid immediately, or, in default, to work three months with the Negroes in chains; this, without any respect of person. Let every one take heed against damage and be warned.
Keywords: COMMITTING CRIME W/ WEAPON - NON-GUN ARMS